2007
DOI: 10.1007/s00269-007-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration experiments on natural omphacites: qualitative and quantitative characterization by various spectroscopic methods

Abstract: Originally published as:Koch-Müller, M., Abs-Wurmbach, I., Rhede, D., Kahlenberg, V., Matsyuk, S. (2007) AbstractA series of natural omphacites from a wide range of P, T occurrences were investigated by electron microprobe (EMP), infrared (IR)-, Mössbauer (MS)-and optical spectroscopy in the UV/VIS spectral range (UV/VIS), secondary ion mass spectrometry (SIMS) and single crystal structure refinement by X-ray diffraction (XRD) to study the influence of hydrogen loss on valence state and site occupancies of ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…The alternative is to directly analyze water in nominally anhydrous mantle minerals of dismembered peridotite bodies (e.g., Miller et al, 1987). Experiments have shown that the substitution type by which hydroxyl is bound in a mineral's structure has a major impact on the diffusivity of hydrogen and, thus, the tendency toward water loss or gain (Blanchard & Ingrin, 2004;Ferriss et al, 2016;Hercule & Ingrin, 1999;Koch-M€ uller et al, 2007;. The greatest problem-water loss due to decompression-applies to any approach because water loss may affect both mantle minerals and melts (plus melt inclusions).…”
Section: General Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative is to directly analyze water in nominally anhydrous mantle minerals of dismembered peridotite bodies (e.g., Miller et al, 1987). Experiments have shown that the substitution type by which hydroxyl is bound in a mineral's structure has a major impact on the diffusivity of hydrogen and, thus, the tendency toward water loss or gain (Blanchard & Ingrin, 2004;Ferriss et al, 2016;Hercule & Ingrin, 1999;Koch-M€ uller et al, 2007;. The greatest problem-water loss due to decompression-applies to any approach because water loss may affect both mantle minerals and melts (plus melt inclusions).…”
Section: General Backgroundmentioning
confidence: 99%
“…Hydrogen is highly diffusive in mantle minerals (e.g., Demouchy & Mackwell, 2006;Koch-M€ uller et al, 2007;Stalder & Skogby, 2003). Hydrogen is highly diffusive in mantle minerals (e.g., Demouchy & Mackwell, 2006;Koch-M€ uller et al, 2007;Stalder & Skogby, 2003).…”
Section: Water Diffusion From Hydrous Mantle Volumesmentioning
confidence: 99%
“…Hydrogen in clinopyroxene is typically observed as one or more of four separate bands in infrared spectra at wavenumbers 3640 ± 10, 3540 ± 10, 3450 ± 10, and 3355 ± 10 cm −1 (Ingrin et al 1989;Skogby 2006;Skogby et al 1990). Despite decades of effort, including systematically doping hydrous diopside (Karimova and Stalder 2013;Purwin et al 2009;Stalder and Ludwig 2007), correlating hydrogen concentration with composition in natural samples (Koch-Muller et al 2004;Skogby et al 1990;Smyth et al 1991), and experimentation Koch-Muller et al 2007;Yang et al 2015), many details of these four hydrogen incorporation mechanisms remain uncertain. Broadly, high-wavenumber bands around 3600 cm −1 bands are most likely related to silica undersaturation and H + charge-balanced by the resulting vacancies and/or trivalent cation substitutions on the tetrahedral site (Karimova and Stalder 2013;Stalder and Ludwig 2007;Su et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Partition coefficients for OH between coexisting garnet and omphacite, using the primary structural water contents of garnet, are 0.07–0.23 (Table ), similar to other studies (discussed by Schmädicke & Gose, ). However, because dehydrogenation of garnet (Wang, Zhang, & Essene, ) and omphacite (Su, Zhang, Redfern, & Bromiley, ) may occur during decompression, the mechanism of hydrogen loss from the crystal structure is different from one to the other (Blanchard & Ingrin, ; Koch‐Müller, Abs‐Wurmbach, Rhede, Kahlenberg, & Matsyuk, ), and the equilibrium partition coefficient is dependent on composition (Bell, Rossman, & Moore, ), the empirical partition coefficients determined in this study may not record equilibrium values related to the peak of UHP metamorphism.…”
Section: Resultsmentioning
confidence: 99%